Governance and competitiveness in global value chains: A comparative study in the automobile and textile industries - Pla-Barber, José; Villar, Cristina (Economics and Business Review, 2019)
In this paper the configuration of the value chains in the automobile and the textile industries building on a theoretical review of the value chain concept, its different typologies and governance models are analised. At the empirical level these chains are classified according to the most relevant participating actors, their interrelations and their methods of upgrading their competitiveness. In both chains a firm-level analysis of their quantitative indicators for competitiveness was carried out. Regarding the automobile industry assemblers generate significant agglomeration economies by attracting international suppliers. The modular production system of the sector generates great flexibility for the manufacturer but it also represents important opportunities for supplier companies aiming to improve their competitive position in these chains. As for the textile industry, our paper shows the clear leadership of the large distribution chains which have radically changed the sector transforming it into an industry driven by the buyers or distributors. Results indicate that the distribution companies are those that have the potential to generate greater added value when these companies have created integrated structures at the end of the chain.